Agreeable Authoritarians: Personality and Politics in Contemporary Russia. (November 2017) - Greene, Samuel; Robertson, Graeme
Personality research is a growing field in political behavior, but most research to date is confined to democracies. We expand the scope to Russia, an authoritarian regime, and find that the impact of personality is substantial but different from the existing literature. We find that agreeableness, a personality trait associated with a desire to maintain positive relations with others that is usually peripheral to politics, becomes the single most important and consistent trait affecting attitudes. This perspective helps us to understand why individuals who are socioeconomically and demographically similar can have quite different attitudes to the regime. Our analysis also helps us to understand the mechanisms through which personality works and how it shapes attitudes to such important elements as religion and state propaganda. Our findings suggest a new, and empirically testable, mechanism behind situations in which regimes rapidly dissolve, including revolutions.